2019
DOI: 10.1089/jop.2018.0130
|View full text |Cite
|
Sign up to set email alerts
|

The Efficacy of 2% Topical Rebamipide on Conjunctival Squamous Metaplasia and Goblet Cell Density in Dry Eye Disease

Abstract: Purpose: To clarify the pharmacological effects of 2% rebamipide eye drops on mucosal membrane functions of the ocular surface epithelium, we investigated keratoconjunctival alterations at the cellular level in this study. Methods: Fifteen patients with definite dry eye disease were recruited from outpatient clinics of the Department of Ophthalmology, Ichikawa General Hospital. The patients received treatment with 2% rebamipide eye drops q.i.d for 12 weeks. Symptom score assessment, tear film breakup time, flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Furthermore, the assessment of CGCs status can significantly contribute to the diagnosis, classification, severity evaluation, and treatment of DED. 62,63 Notably, the use of evaluation methods for assessing CGCs can yield widely varying results, apart from factors such as age, sex, and disease characteristics. Given the significance of CGCs in DED, we covered imaging methodological developments in the visual assessment of CGCs below.…”
Section: Changes In Conjunctival Goblet Cells In Dry Eye Diseasementioning
confidence: 99%
“…Furthermore, the assessment of CGCs status can significantly contribute to the diagnosis, classification, severity evaluation, and treatment of DED. 62,63 Notably, the use of evaluation methods for assessing CGCs can yield widely varying results, apart from factors such as age, sex, and disease characteristics. Given the significance of CGCs in DED, we covered imaging methodological developments in the visual assessment of CGCs below.…”
Section: Changes In Conjunctival Goblet Cells In Dry Eye Diseasementioning
confidence: 99%
“…Compromised epithelial barrier function is also related to aging and hence, strengthening the epithelial barrier is not only essential in allergic keratoconjunctivitis, but also in all forms of DED. Significantly, the anti-oxidative activity of 2% Rebamipide has been shown to stabilize the corneal epithelial barrier [85,86].…”
Section: Compromised Epithelial Barrier In Ocular Surface Disease (M ...mentioning
confidence: 99%
“…There are many studies that show its effectiveness in the treatment of DED. REB ophthalmic suspension (1% and 2%) has shown significant improvements in corneal and conjunctival staining, as well as tear film break-up time (TBUT) [20][21][22][23][24]. Igarashi et al [25] reported an improvement in DED symptoms and signs among contact lens (CL) wearers.…”
Section: Introductionmentioning
confidence: 99%